Implementation of Regulatory Supervision Regional Head (DPRD) in Dumai City - Zulhidayat, Muhammad; Elmayanti , Elmayanti; Zulwisman, Zulwisman; Separen, Separen; Musliadi, Ricki; Yozani, Riyanda Elsera (Ipso Jure, 2025)
The Regional Head Regulation in the hierarchy of laws and regulations can be interpreted through Article 8 paragraphs (1) and (2) of Law Number 12 of 2011 concerning the Establishment of Laws and Regulations. The existence of this Regional Head Regulation also raises several record problems, Regional Head Regulations have potential problems no less complicated than Regional Regulations. This is because the supervision of the Regional Head Regulation by the DPRD in Dumai City is not yet clear whose authority. Therefore, this study seeks to analyze how supervision of Regional Head Regulations is made in the context of delegation from higher laws and regulations as well as in the context of policy rules (beleidsregel). This research uses empirical juridical research methods. The results of this study show that the Dumai City DPRD has not been able to supervise the Regional Head Regulation made by the Mayor of Dumai. The suggestion in this study is that there must be clear rules regarding the authorities in supervising the Regional Head Regulation.